Kontribusi Makanan Sepinggan Sebuah Kantin Sekolah di Jakarta dalam Pemenuhan Kebutuhan Gizi Siswa SMP - Ros Maria Andesko; Nurheni Sri Palupi; Didah Nur Faridah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
Nutrient recommendation in school meals should meet about (80-120)% out of a third of the requirement daily adolescent intake. School canteen should provide healthy and nutritious balanced meals. This study was conducted in one school canteen in Jakarta to (1) determine nutritional quality of school meals, (2) assess adequency level of nutrient, (3) comparing adequency level of nutrient in group of Indonesian menus and international. Conversion of food weight or its composition into nutritional value was used for determining nutritional quality, using references from Tabel Komposisi Pangan Indonesia 2009, Informasi Kandungan Gizi Pangan Jajanan Anak Sekolah BPOM 2013, and ASEAN Food Compo-sition Database 2014. Adequency level was assesed by comparing nutrient value with students needs. The school meals had average for carbohydrate content (57.0±20.4 g), protein (16.6±5.7 g), fat (16.9±9.1 g), energy (454±147 kcal), vitamin A (134±111 mcg) and iron (3.0±1.7 g). More than 56% of school meals were did not meet the standard. Indonesian and international menus had average for carbohydrate content (53.2±17.9 g; 58.7±21.2 g), protein (17.9±6.0 g; 16.1±5.7 g), fat (15.3±7.7 g; 17.7±9.8 g), energy (427±142 kcal; 466±146 kcal), vitamin A (139±130 mcg; 131±103 mcg) and iron (4.5±2.1 mg; 2.3±1.3 mg).